CRITICAL DISCOURSE ANALYSIS ON THE 2020-2024 RPJMN: ON CLIMATE CHANGE AND FOOD SECURITY - Himawan Indrajat; Pitojo Budiono (Proceedings International Indonesia Conference on Interdisciplinary Studies, 2025)
This article examines the 2020-2024 National Medium-Term Development Plan (RPJMN) with a critical discourse analysis approach, especially related to the issues of climate change and food security. The RPJMN as a national strategic planning document contains various development policies and priorities that are a reference for the Indonesian government in facing the challenges of sustainable development. This research aims to uncover how the discourse on climate change and food security is constructed in the document, as well as how the government's commitment and strategy are reflected through the language and policy structure carried out. The critical discourse analysis method was used to examine the text of the RPJMN in depth, identifying the main themes, underlying ideologies, and social and environmental implications of the proposed policies. The results of the analysis show that the 2020-2024 RPJMN places climate change and food security as strategic national priorities, with an emphasis on sustainable human and economic development. However, there are indications of the need to strengthen policy implementation so that the targets that have been set can be achieved effectively. This paper makes an important contribution to understanding the dynamics of Indonesia's national policies in the context of climate change and food security, while offering a critical perspective that can be the basis for future policy evaluation and development. Thus, this research is not only relevant for academics and policymakers, but also for stakeholders involved in sustainable development in Indonesia.(National Medium-Term Development Plan 2020-2024) (Strategic Policy on Food Security and Nutrition 2020-2024)